2009
DOI: 10.1021/ie801848x
|View full text |Cite
|
Sign up to set email alerts
|

Porosity Development in Activated Carbons Prepared from Walnut Shells by Carbon Dioxide or Steam Activation

Abstract: The influence of carbon dioxide and steam as activating agents on the porosity development of activated carbons produced from walnut shells was investigated. The study was made covering a wide range of burnoff (12−76%) and employing different temperatures and times: in carbon dioxide activation, 850 °C varying the activation time in the range 60−480 min, and in steam activation, 700, 850, and 900 °C (for 30−120 min). It was found that the gasifying agent has a profound influence on the activated carbon porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(61 citation statements)
references
References 38 publications
8
53
0
Order By: Relevance
“…The CQuest biochar's small initial surface area (0.75 m 2 g −1 ) indicated that pores were filled with volatile organic materials (Mukherjee et al, 2011), which are susceptible to mineralization and volatilization over time Kim et al, 2011). The disappearance of these organics with soil aging likely (i) increased porosity and surface area akin to the effect that activation has on charcoal (González et al, 2009;Yang et al, 2010); and (ii) increased negatively charged sites on biochar (Cheng et al, 2008). The charged sites can bind NH 4 -N, making inorganic N less available for microorganisms and leaching (Lehmann et al, 2003;Steiner et al, 2008;Dempster et al, 2012).…”
Section: Mechanism By Which Biochar Effects Soil Processesmentioning
confidence: 99%
“…The CQuest biochar's small initial surface area (0.75 m 2 g −1 ) indicated that pores were filled with volatile organic materials (Mukherjee et al, 2011), which are susceptible to mineralization and volatilization over time Kim et al, 2011). The disappearance of these organics with soil aging likely (i) increased porosity and surface area akin to the effect that activation has on charcoal (González et al, 2009;Yang et al, 2010); and (ii) increased negatively charged sites on biochar (Cheng et al, 2008). The charged sites can bind NH 4 -N, making inorganic N less available for microorganisms and leaching (Lehmann et al, 2003;Steiner et al, 2008;Dempster et al, 2012).…”
Section: Mechanism By Which Biochar Effects Soil Processesmentioning
confidence: 99%
“…This is accompanied by the creation of a group of crossed transformed chains as the product becomes enriched with carbon, which increases rigidity and creates porosity [3,4]. However, this porosity can be closed by deposits of tars, which are residuals of the carbonisation process, necessitating the use of an activating gas or a mixture of gases of activating gases to open and develop new porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Etching is so severe at 900 °C, that the {111} planes are no longer able to be distinguish after CO2 activation. In the case of activated carbon, CO2 first produces narrow micropores and then the pores are widened as activation progresses [15][16][17][18][19][20]. If the mechanism of CO2 activation of BDD is similar to that of activated carbon, then the activation at 900 °C can be attribute to the widening of the nanopits to form large (200-400 nm) square pits.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to O2 and H2O, CO2 is also a common oxidative etchant. CO2 activation has been widely used to prepare activated carbon, and is known to lead to activated carbon with a different microstructure compared to steam activation [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%